2017
DOI: 10.1007/s00015-016-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the full-scale emplacement (FE) experiment at the Mont Terri rock laboratory

Abstract: Opalinus Clay is currently being assessed as the host rock for a deep geological repository for high-level and low-and intermediate-level radioactive wastes in Switzerland. Within this framework, the 'Full-Scale Emplacement' (FE) experiment was initiated at the Mont Terri rock laboratory close to the small town of St-Ursanne in Switzerland. The FE experiment simulates, as realistically as possible, the construction, waste emplacement, backfilling and early post-closure evolution of a spent fuel/ vitrified high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…They are required both to validate the safety functions and to investigate the processes taking place after closure of the repository. Worldwide, only a few heated real-scale tests have been launched: the prototype repository experiment in crystalline rock at Äspö, Sweden (Johannesson et al , 2007; Dohrmann & Kaufhold, 2014; Svemar et al , 2016), the PRACLAY experiment in Boom Clay at the HADES rock laboratory in Belgium (Bernier et al , 2007), the ALC (full-scale demonstrations experiment at Bure URL) experiment in Callovo-Oxfordian Clay at ANDRA's rock laboratory in France (Gugala, 2015), the recently installed FE experiment (full-scale emplacement experiment) in Opalinus Clay at Mont Terri in Switzerland (Müller et al , 2017) and the FEBEX test investigated in the present study.…”
mentioning
confidence: 99%
“…They are required both to validate the safety functions and to investigate the processes taking place after closure of the repository. Worldwide, only a few heated real-scale tests have been launched: the prototype repository experiment in crystalline rock at Äspö, Sweden (Johannesson et al , 2007; Dohrmann & Kaufhold, 2014; Svemar et al , 2016), the PRACLAY experiment in Boom Clay at the HADES rock laboratory in Belgium (Bernier et al , 2007), the ALC (full-scale demonstrations experiment at Bure URL) experiment in Callovo-Oxfordian Clay at ANDRA's rock laboratory in France (Gugala, 2015), the recently installed FE experiment (full-scale emplacement experiment) in Opalinus Clay at Mont Terri in Switzerland (Müller et al , 2017) and the FEBEX test investigated in the present study.…”
mentioning
confidence: 99%
“…The GBM and pellet mixtures presented in this review comprise several bentonite materials, mainly MX-80, Serrata, Kunigel (V1 and GX), FoCa, and GMZ. MX-80 GBM from Wyoming, USA, is a sodium montmorillonite bentonite and was adopted by NAGRA in the FE experiment [7]. Serrata GBM produced from bentonite deposits (the same origin as FEBEX bentonite) in the zone of Serrata (Almería, Spain) was used in the EB experiment at the Mont Terri rock laboratory [8].…”
Section: Granulated Bentonite Mixtures (Gbm)mentioning
confidence: 99%
“…It was shown that the fraction of fines could be an important factor to achieve higher compaction dry density. The best mixture was used in the FE experiment at the Mont Terri rock laboratory [7] where the target DD of 1.45 g/cm 3 was achieved.…”
Section: Compaction Propertiesmentioning
confidence: 99%
See 2 more Smart Citations